MANAJEMEN PENGOLAHAN DATA ADMINISTRASI KEUANGAN SEKOLAH MENGGUNAKAN METODE GROUNDED RESEARCH - Suwardi Suwardi; Suprapti Suprapti; Danang Danang (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2020)
The administrative financial data processing management system at SMP N 17 Semarang is carried out by students coming directly to pay to the Administration, because the use of 1 existing computer facility in the Principal's room and 3 computer facilities in the Administration room makes payment data recorded in a book. big. The data used in SMP N 17 Semarang still uses manual recording or bookkeeping, which can result in errors in recording payments with the same student's name, data easily lost or torn. The Grounded Research method is expected to be able to produce quality management information to support management policies. In addition, with good management of administrative activities, it is hoped that it will be able to provide comfort for students and parents of guardians in making transactions. To anticipate the occurrence of tuition payment services that are slow, not fast and inaccurate due to the large number of student payments. Seeing the duties and functions that must be carried out by administrative officers of SMP N 17 Semarang to hold a School Information system, the authors built a School Management Information System as an alternative to make it easier for administrative officers to input new student admissions, student data collection and tuition payments. which is in SMP N 17 Semarang.